Second Five Year Plan Punjab State Review of Progress for 1956-61 - Planning Commission (Planning Commission, 1956)
During the last ten years of planned development in the wake of the upheaval caused by the partition, the economy of Punjab State has advanced in many directions and registered considerable progress in almost all this major sectors. The strategy followed by the State has all along been in consonance with the broad priorities decided for the country as a whole and the adjustments that have been made were necessitated by the particular circumstances obtaining in the State. The results achieved during this decade have assisted in filling the gaps which were caused by the partition and have also provided the base for all round economic development which is the objective behind the plan. The task was vast in magnitude and was beset with serious difficulties but the agencies concerned with the execution of the plan schemes took up the challenge with a sense of awareness and urgency. As a result, the performance during both the plan periods has been of a very satisfactory order.
Review of Progress for 1956-61
Government of Punjab